A New Approach for Stage 2 Adult Acquired Flatfoot Deformity. Issue 1 (January 2022) - Raduan, Fernando C.; Coetzee, J. Chris; Den Hartog, Bryan D.; Seybold, Jeffrey D.; Cammack, Paul M.; Stone, Rebecca M.; Fritz, Jacquelyn E.; Seiffert, Kayla
Category: Hindfoot Introduction/Purpose: Adult Acquired Flatfoot Deformity (AAFD) is a common progressive pathology that mainly affects patients after their 50s. Even though it is not clear yet what causes AAFD, the great majority of patients have their talonavicular (TN) joint sub dislocated in one or more planes. According to the severity of the deformity and its flexibility, different surgical procedures can be performed to realign the foot. The deformities usually happen around the TN joint, making it the center of rotation and angulation (CORA). Corrections on the CORA realign deformities in different planes and his concept can be applied to mostly any deformity. The objective of this study is to evaluate clinically and radiographically patients with stage 2 AAFD submitted to isolated TN fusion. Methods: Fifty-four patients (59 feet) from July 2013 to December 2019 with stage 2 AAFD were submitted to isolated TN fusion. All patients had clinical deformity and arch foot collapse associated with pain along the medial hindfoot. Weight-bearing x- rays were performed pre-operatively, the Meary's and calcaneal pitch angles were measured on lateral view and the Talar coverage and Simmon's angle were measured on antero-posterior view. Angles were measured by a fully trained foot and ankle surgeon. Post-operative measurements were done with the same set of images by the same surgeon, one month after the initial measurements. FAAM and VR12 were used to compare patient's clinical status. Patients with previous surgeries on the foot or ankle and patients submitted to other fusions or hindfoot osteotomies were excluded from the study. Gastrocnemius lengthening and toes corrections were not an exclusion criterion. Results: Thirty-seven females and seventeen males were evaluated with a mean age 61 years at the time of surgery. Only the FAAM score significantly improved from pre-operative (FAAM = 48.48, VR-12 Mental = 55.73, VR-12 Physical = 37.25) to most recent mean follow-up of 16.2 months (FAAM = 58.45 (p<.001), VR-12 Mental = 57.19 (p=.179), VR-12 Physical = 37.53 (p=.832). The lateral view X-Rays showed Meary's and calcaneal pitch angles mean improving from 27 and 15 degrees pre-operatively to 9 and 18 degrees post operatively (p<.001), whereas Front view foot X-Rays showed Talo-Naviciular coverage angle and Simmon's angle going from 35 and 20 degrees to 5 and 6 degrees respectively (p<.001) Conclusion: Isolated talonavicular fusion can correct the deformity on its multiple planes providing not only significant improvement on radiographic alignment but also the FAAM clinical outcome score. Comparative studies should be performed to determine which is the best technique for patients with stage 2 AAFD.